To wear a fae crown eaudiobook - Odette, Tessonja (Fair Isle Trilogy, 2021)
Every young woman dreams of wearing a crown. But never a fae crown. Because the crowns of fae are forged with blood. Being the forced bride of a fae king was supposed to be torture. King Aspen was supposed to be my enemy. But I was wrong about him. So wrong I think I might be in love with him. With our wedding just three days away, we are closer than ever to securing the treaty between the humans and fae. But when my past becomes grounds for invalidating our alliance, war looms yet again. I'm the only one who can save the Fair Isle. If I do it, I'll have to give up the man I love. Return to the human realm. Face death. I swore I'd do anything to save my people. But who are my people? The answer should be easy. The humans. There's just one problem. I might not be human after all . . .